EFEKTIFITAS PELAKSANAAN KEBIJAKAN ELECTRONIC-KARTU TANDA PENDUDUK (E-KTP) DI KECAMATAN TAMPAN BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2006 TENTANG ADMINISTRASI KEPENDUDUKAN - Jusmar '; Mexsasai Indra; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The dynamics of the problems that arise regarding the application of e-ID card first so many problems there are indications in the provision of e-ID card project Such corruption, the second problem is the fact that quite interesting that the refusal by some private banks in Indonesia with the reason the E-ID card KTP is not the same as the previous, the third problem is: Based on the mandate of Article 63 Paragraph (3) of Law No. 23 Year 2006 concerning Population Administration Electronic Identity Card (e-ID) applies nationally, but in the case praktenya tersbut difficult to embodied, while the fourth issue is the implementation of e-ID card lifetime. Of the four issues above authors writing thesis proposal is focused on the problems that all third and fourth course this has a correlation with the author angkat.Ini title that attracts writers to lift the title: "The Effectiveness of Policy Implementation Electronic- identity This study aims to Know implementation-implementation of Electronic Identity Card (e-ID) in District Charming by Act No. 23 of 2006 on Population Administration and for the implementation of the application Electronic- Knowing Problems of Identity Card (e-ID) in District HandsomeBased on the formulation of the problem and research objectives, the type of research that is used by the author is the law of sociological research is the study of the effectiveness of the laws that are applicable in this case I do research on Analysis Scope of application Electronic- Identity Card (e-ID) Under Law Law No. 23 Year 2006 concerning Population Administration in Pekanbaru. The results of this study indicate Implementation of policy implementation-Electronic Identity Card (e-ID) in District Handsome pursuant to Law No. 23 Year 2006 concerning Population Administration was less effective it was proven by the many people who until now have yet to receive E -KTP it proved there were 3858 people Handsome District residents who still do not get an e-ID card and Policy Issues E-KTP implementation of the sub-districts, namely the lack of socialization Handsome government to remote areas, causing uneven implementation of policy information as well as e-KTP. Which is where this policy also does not meet the government's target when viewed from the Law of the Republic of Indonesia.Keywords: Effectiveness, Electronic Identity Card, Legal Due